Water allocation management in the Yellow river basin: Potential for water trading? - Cai, Ximing; Yang, Yi-Chen E.; Jianshi, Zhao; Ringler, Claudia (International Food Policy Research Institute, 2010)
Management of the Yellow River Basin (YRB) is critical for China’s agricultural production and socioeconomic development. The cultivated area in the basin is about 13 percent of the total cultivated area in China, but the basin holds only 3 percent of the country’s water resources. At the same time, the basin provides water to an estimated 150 million people—both inside and outside the basin area—and rapidly growing industries in the downstream area and, more recently, the midstream area, where mining and chemical industries are expanding. As a result, the basin faces severe water shortages. To address decades of river-flow cutoffs, the government enforced the cross-provincial, quota-based Water Allocation Agreement of 1987 through Unified Water Flow Regulation (UWFR) in 1999. This policy was in line with the past decade’s renewed focus on sustainable water use and efforts by the Government of China to keep the Yellow River “healthy.” The UWFR, however, did not take into account the value of water in various uses, and water users forced to give up water resources—primarily irrigators in the upstream and midstream provinces—were not compensated.